الألعاب التعليمية ودورها في تنمية التفكير الابتكاري لدى تلميذ مرحلة التعليم الاساسي من وجهة نظر المعلمين (Journal of Academic Research, 2020)
Summary of the study(Educational games and their role in the development of innovative thinking of the basic education pupil from the perspective of teachers)This study aims to identify the extent of the contribution of educational games in the development of innovative thinking among the pupils of basic education, and identifies the problem of study in the following question:What is the contribution of educational games to the development of innovative thinking for the first grade pupil of basic education from the point of view of teachers in Misrata?The study also used the descriptive approach to suit the nature of the current study. The sample of the study was determined from (200) randomly selected teachers. The study also used the questionnaire as a tool. Experienced and for the competence, and calculation of the coefficient of stability using the coefficient Alvakronbach, where the coefficient of total stability of the tool (0.82%). To reach the results, the researcher used the following statistical methods: percentage weight, weighted mean and standard deviation.The results of the study showed the following:- Most of the paragraphs of the tool came with a high percentage as the highest paragraph obtained(Develop students' cognitive ability) on a weighted mean (2.90) and a percentage weight(61.5), This shows that educational games play an important role in the development of cognitive ability of students, andexpand their cognition, and the ability to focus and attention, and create a kind of spiritual and emotional renewal, it also instills the concept of cooperation.- The least paragraph (which develops the ability to solve problems in creative ways) obtained a weighted medium (1.33) and weight percentage (5.39). So that he can overcome various cognitive problems in a creative way.- The study also found that despite the importance of educational games within the classroom educational environment, but they are not available in most schools and classrooms, and the lack of dependence of teachers despite their emphasis on the importance and role in the development of the educational process